Properties of homogenous particleboard from (Gliricidea sepium) / Nadiah Jumhuri and Suzana Amran - Jumhuri, Nadiah; Amran, Suzana (2006)
In the study, are used three resin content of formaldehyde (UP) 8%, 10% and 12%. The particle sizes used are 0.5, 1.0, 2.0 mm and the wax content of 1%. The result showed that with increasing content all the mechanical properties increased with the physical properties are greatly improved. Wax additive decrease the mechanical properties and improved the physical properties. However all boards do not meet the minimum requirement for MOR, MOE, WA, and TS as stipulated the BS standards.